Rādhāmādhavavilāsacampūḥ - Jayarāma Piṇḍye, fl. 1654-1673 (SAMP early 20th-century Indian books project, 1922)
In praise of Shahji Bhonsle, 1594-1664, father of Shivaji, Raja, 1627-1680, Maratha ruler.